2017
DOI: 10.5604/01.3001.0010.1021
|View full text |Cite
|
Sign up to set email alerts
|

Role of intraoperative neuromonitoring of the recurrent laryngeal nerves during thyroid reoperations of recurrent goiter

Abstract: Reoperations of the thyroid gland are challenging to any surgeon. Such procedures are technically difficult and involve higher risk of complications than primary procedures. Recurrent laryngeal nerve (RLN) palsy is one of such complications The aim of the study was to evaluate the effectiveness of intraoperative neuromonitoring (IONM) in preventing RLN palsy during recurrent goiter operations. Material and methods. We retrospectively analyzed the results of thyroid reoperation performed at the Department of En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…In the literature, many studies have investigated RLN identification, dissection, and exposition in thyroid reoperations. In redo surgery, anatomy, anatomical changes, monitoring, morbidity, complication rate, and IONM have been studied regarding only the RLN [61011122930]. Contrary to identification of the EBSLN in primary cases, we could not find any publication about visual and functional identification and electrophysiological monitoring of the EBSLN in redo thyroid surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the literature, many studies have investigated RLN identification, dissection, and exposition in thyroid reoperations. In redo surgery, anatomy, anatomical changes, monitoring, morbidity, complication rate, and IONM have been studied regarding only the RLN [61011122930]. Contrary to identification of the EBSLN in primary cases, we could not find any publication about visual and functional identification and electrophysiological monitoring of the EBSLN in redo thyroid surgery.…”
Section: Discussionmentioning
confidence: 97%
“…However, nerve visualization is not easy while dissecting scar tissue during thyroid reoperations. Therefore, the risk of injury to both superior and inferior laryngeal nerves is a major concern of redo surgery [1011].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the risk of RLN injury is the major concern of reoperative thyroid surgery. Such procedures are technically difficult and involve a higher risk of complications than do primary procedures [ 2 , 3 ]. Thyroid reoperations can be challenging, even for a highly experienced thyroid surgeon, as visual identification of the RLN is more difficult during dissection of scar tissue than in the virgin neck [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Sopinski et al 23 average duration of surgeries was found shorter in the nerve monitoring group (71.29 ± 17.125 minutes and 75.75 ± 17.94 minutes for monitored and non-monitored groups, respectively.) but it was not statistically significant (P=0.377).…”
Section: Discussionmentioning
confidence: 85%